Efektivitas Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Pemahaman Konsep Matematika Siswa - Ramadhani, Muhammad Habib; Sari, Ratna; Agung, Anugrah; Izzania, Rizqa Dwi Shofiya Maghfira (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effectiveness of the Jigsaw cooperative learning model in improving students’ conceptual understanding of mathematics. The background of this research is based on the low ability of students to deeply understand mathematical concepts, as indicated by the dominance of procedural-based learning and the lack of active learning interactions. This study employed a quasi-experimental method with a posttest-only control group design. The sample consisted of two tenth-grade classes at SMA Muhammadiyah 1 Metro, designated as the experimental and control groups. The instrument used was a set of five essay questions on trigonometry. Data was collected using a mathematical concept understanding test and analyzed descriptively quantitatively. The results showed that the average conceptual understanding of mathematics in the experimental class was higher than that of the control class. The t-test result yielded a P-Value = 0.012 < 0.05, indicating a significant difference between the two groups. These findings suggest that the Jigsaw model is effective in enhancing students’ conceptual understanding in mathematics. This model can serve as an alternative instructional strategy that promotes active engagement, collaboration, and conceptual reinforcement, particularly in abstract topics such as trigonometry